SWOT and TQM Based Elementary School Development Strategy through Charismatic Leadership: A Case Study at State Elementary School (SDN) 1 Banteran - Nur'aeni, Fatmah; Yusuf, Enjang Burhanudin (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
This study aims to explain primary school development strategies through the integration of SWOT analysis, Total Quality Management (TQM) approach, and charismatic leadership of the principal. The study was conducted at SDN 1 Banteran, Banyumas Regency, using a qualitative approach and case study method. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman interactive model. The results showed that SWOT analysis was used in a participatory and reflective manner to develop strategies based on internal strengths and responses to external challenges. TQM is implemented through a consistent PDCA cycle, active involvement of teachers and parents, and the strengthening of a comprehensive quality culture. The principal's charismatic leadership acts as a catalyst for change, bridging the gap between strategic diagnosis and policy implementation through inspirational communication, modeling and strengthening collective spirit. The integration of these three approaches forms an adaptive, collaborative and results-oriented strategic management model for primary schools. This research found a GAP in previous studies that tended to separate the roles of SWOT, TQM and charismatic leadership separately. This study closes the gap by presenting an integration that is operational and contextualized. The model of SDN 1 Banteran can be used as a reference for the development of other primary schools in building a quality, participatory and sustainable education system.